(untitled) (Al-Qamar, 2025)
Cruelty towards animals is not a new issue in our society. However, the persistence of this cruelty, despite our identity as a Muslim society, shows our failure to adhere to the teachings of Islam regarding animal welfare. Although there are legal frameworks and mechanisms in place to prevent the mistreatment and cruelty with animals, they are outdated and ambiguous in its scope. This research highlights the major issue of mistreatment and cruelty with stray animals in Pakistan and critically examines the existing legal framework designed to protect animals. Through the use of a qualitative approach, this study integrates Islamic teachings with the current legal framework in order to provide comprehensive insights into the animal welfare. This research concludes that the existing legal mechanisms are insufficient and unable to cover all animals and it need to be updated to address our contemporary societal issues. It must be aligned with the injunction of Islam as laid down by the Holy Qur’an and Sunnah.